Asuhan Keperawatan Pada Tn. W Keluarga Ny. C dengan Gangguan Sistem Persyarafan : Stroke di Desa Kalibuntu RT 01 RW 01 Kecamatan Losari Kabupaten Brebes - Sai Nur Hidayah; Ahmad Zakiudin; Esti Nur Janah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Stroke is a disease that causes nerve damage caused by bleeding or blockage in the affected part of the brain. This disease can cause disability or death. According to the World Health Organization (WHO), there has been a significant increase in deaths due to stroke since 2000, from 2 million to 8.9 million (11%) in 2019. Data from the Kecipir Health Center, stroke sufferers in Kalibuntu village were 20 people out of 2560 (0 .08%) the number of productive residents experienced a stroke. The results of the patient's assessment showed that his right hand had not been able to move since 6 years ago and his right leg also experienced weakness in movement so that it was difficult for him to walk. The nursing diagnoses raised were knowledge deficit, impaired physical mobility and ineffective family health management.